The Degree of Practice of Authentic Assessment Strategies and their Instruments by Science Teachers of the Basic Stages from their Perspectives - Musallam, Asma' M; Khataibeh, Abdullah M. (Dirasat: Educational Sciences, 2023)
Objectives: This study aimed to identify the degree of science teachers' practice of authentic assessment strategies and its instruments from their perspectives. Methods: To achieve the study's objectives, a descriptive survey approach was used. A questionnaire was developed and then distributed to an accessible sample of science teachers in the schools of the Directorate of Education- Qasbah Amman, comprising (208) male and female teachers. Results: The results showed that the overall degree of science teachers' practice of authentic assessment strategies and instruments was high. Furthermore, statistically significant differences were found in the average degree of practice attributed to the variables of gender and attending training courses in the field of educational sciences. However, there were no statistically significant differences in the average degree of practice attributed to the variables of academic qualification and teaching experience. Conclusions: The study recommended conducting training courses to help science teachers understand and implement all authentic assessment strategies and instruments, rather than being limited to specific ones.